Layanan KOBE “Konsultasi Belajar” Untuk Meningkatkan Literasi Baca Tulis Siswa Sekolah Dasar - Rahayu, Ni Komang Ari; Septiari, Ni Kadek; Dewi, Ni Kadek Riska; Sari, Ni Komang Desy Artika; Putri, Ni Kadek Mirah Atmanadi; Asmini, Ni Ketut Sri; Werang, Basillius Redan (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
The urgency of this study is to determine the benefits of learning consulting services in improving students' literacy at SD Negeri 4 Patas, Buleleng Regency. This study uses a qualitative approach with a case study design. This research will combine two qualitative research traditions, namely phenomenology and instrumental case studies. In this study, inductive data analysis is carried out through data collection, data analysis, reduction, presenting data that has been sorted, and drawing conclusions or verifying findings. Research data sources involve primary data sources, consisting of school principals, teachers, students, and other parties related to the problem being researched. The results of the study showed that literacy skills were low at SD Negeri 4 Patas, with only 34% of students reaching the KKM standard. The causes include low interest in reading, limited reading media, and reading difficulties. The proposed solution is the